2020
DOI: 10.1111/bcpt.13426
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and longevity genes in cardiovascular diseases

Abstract: Over the last century, Western societies experienced a demographic shift driven by increased lifespan and decreased fertility, resulting in the subversion of the world's demographic pyramid. In ageing societies, cardiovascular diseases are the major cause of morbidity and mortality, thus representing a major societal and economic burden. Indeed, ageing associates with the deterioration of a genetic network implicated in senescence and longevity, orchestrating deleterious cellular processes that converge in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 122 publications
0
22
0
Order By: Relevance
“…As such, mechanisms involved in ageing hold potential as therapeutic targets for age‐tailored management of ischaemic cerebral events. 25 Over the last years, we and others showed that ageing, vascular dysfunction and age‐dependent cardio‐ and cerebrovascular diseases involve similar pathophysiological processes including the production of reactive oxygen species and the surge of inflammation. 16 , 19 , 20 , 26 , 27 , 28 Indeed, age associates with an augmented chronic smouldering innate immune response, known as inflamm‐ageing, that occurs in the absence of appropriate inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…As such, mechanisms involved in ageing hold potential as therapeutic targets for age‐tailored management of ischaemic cerebral events. 25 Over the last years, we and others showed that ageing, vascular dysfunction and age‐dependent cardio‐ and cerebrovascular diseases involve similar pathophysiological processes including the production of reactive oxygen species and the surge of inflammation. 16 , 19 , 20 , 26 , 27 , 28 Indeed, age associates with an augmented chronic smouldering innate immune response, known as inflamm‐ageing, that occurs in the absence of appropriate inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…When FoxO activity is compromised throughout the oxidative stress it becomes advantageous for cell survival. For example, knockout of FoxO3a or FoxO1 can reduce ischemia‐induced infarct size in brain to some extent 42 . Ma et al, elucidated that up‐regulated miR‐96‐5p expression would inhibit apoptosis by targeting FoxO1 in hepatocellular carcinoma 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings might have translational value in the highly susceptible and affected elderly population, which is paradoxically under-represented in clinical trials. Of interest, in both rodents and humans, aging associates to a chronic low-grade activation of the innate immune system in absence of appropriate immunogenic stimuli 51 . Such a dysfunctional process is termed «inflamm-J o u r n a l P r e -p r o o f aging» and thought to play a major role in several age-associated CV diseases including ischemic stroke 52 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%